Implementation of Group Investigation Cooperative Learning Model in Increasing student learning participation - Ahmad Yudianto; Askar Askar; Moh. Ali (Department of Islamic Education, Postgraduate Program State Institute for Islamic Studies Palu, 2020)
The aim of this paper is to discusses the practice of cousin marriage in the community of Kalola Village, Pasangkayu Regency, West Sulawesi. This study uses qualitative methods and data was gathered through observation, in-depth interviews, and written material. Data analysis was analyzed using a grounded theory approach. The results showed that the learning participation of students in the implementation of the cooperative learning model type Group Investigation before, namely: from 20 students that, the results of student participation in interaction activities were classified as low seeing the students, compiling only 7 people, responding (asking and answering ) only 5 people and accepted in the teacher's explanation only 10 people and and the indicator of students' learning participation was low as seen from the skill scores of these students, while after the implementation of the cooperative learning modeltype group investigation experienced a significant increase, there were 20 students. That the results of student participation in interaction activities compose 19 people, respond (ask and answer) 14 people, and accept in the teacher's explanation 14 people and indicators of increasing student learning participation also increase, it can be seen that the skill value of these students.